Impact of Corporate Governance on the Efficiency of Managing Working Capital in the Manufacturing Sector in Jordan - Abu Khalaf, Bashar; Al-Tarawneh, Alaaeddin (Jordan Journal of Business Administration, 2019)
The main objective of this research is to investigate the effect of corporate governance on working capital proficiency. A sample of 49 manufacturing organizations listed in ASE during the period (2005-2016) is used. This research uses panel analysis (fixed- and random - effect techniques) in order to empirically investigate the impact of corporate governance on managing working capital efficiently. The model includes two variables of corporate governance; CEO tenure duration and board size and the model is controlled by including firm size, growth and performance. The results suggest that the more experience the CEO has and the smaller the board size is, the better the governance of manufacturing companies in Jordan would be in managing their working capital efficiently. In addition, large, high - growth companies efficiently manage their working capital in a better way. Lastly, high - profitability manufacturing companies in Jordan tend to ignore managing their working capital efficiently.